An unusual case of obstructive jaundice - Sharma, P; Subedee, A; Khadka, H; Pradhan, S; Lohani, B; Joshi, BR; Paudel, S (Journal of Institute of Medicine Nepal, 2007)
Abstract: A case of hydatid cyst of liver rupturing into biliary tree causing obstructive jaundice isreported. Key words: Obstructive jaundice, hydatid cyst ERSP The full text of this paper is available at Journal of Institute of Medicine website